Effects of active video games on children and adolescents: A systematic review with meta-analysis - Oliveira, Crystian B. [UNESP]; Pinto, Rafael Z. [UNESP]; Saraiva, Bruna T. C. [UNESP]; Tebar, William R. [UNESP]; Delfino, Leandro D. [UNESP]; Franco, Marcia R.; Silva, Claudiele C. M. [UNESP]; Christofaro, Diego G. D. [UNESP] (Wiley, 2020)
Objective: To investigate the effectiveness of active video games (AVGs) on obesity-related outcomes and physical activity levels in children and adolescents. Design: Systematic review with meta-analysis. Methods: Literature search was performed in five electronic databases and the main clinical trials registries. Randomized controlled trials investigating the effect of AVGs compared with no/minimal intervention on obesity-related outcomes (body mass index [BMI], body weight, body fat, and waist circumference) and physical activity levels of children and adolescents were eligible. Two independent reviewers extracted the data of each included study. PEDro scale was used to assess risk of bias and GRADE approach to evaluate overall quality of evidence. Pooled estimates were obtained using random effect models. Results: Twelve studies were considered eligible for this review. Included studies mostly reported outcome data at short-term (less or equal than three months) and intermediate-term follow-up (more than 3 months, but <12 months). AVGs were more effective than no/minimal intervention in reducing BMI/zBMI at short-term (SMD = −0.34; 95% CI: −0.62 to −0.05) and intermediate-term follow-up (SMD = −0.36; 95% CI: −0.01 to −0.71). In addition, AVGs were more effective in reducing body weight compared with no/minimal intervention at intermediate-term follow-up (SMD = −0.25; 95% CI: −0.46 to −0.04). Regarding physical activity levels, AVGs were not more effective compared with minimal intervention at short-term and intermediate-term follow-up. Conclusions: Our review identified that AVGs were better than minimal intervention in reducing BMI and body weight, but not for increasing physical activity in young people.
Keywords: active video game; adolescents; children; obesity; physical activity